Performance measurement link between the balanced scorecard dimensions: an empirical study of the manufacturing sector in Malaysia - Krishnan, Anbalagan (Inderscience Publishers, 2014)
In today’s competitive business environment, firms are emphasising the use of an integrated performance system consisting of both financial and non-financial measures. The emphasis on non-financial measures that drives the financial outcome adds value to the strategic goals of organisation. Literature highlights the causal relationship between the financial and non-financial performance and empirically examined in the Western context but seems to be still lacking in Malaysia. Therefore, this study explores the association between the financial and non-financial measures in the context of the Malaysian business environment. This study uses the structural equation modelling (SEM) which is a superior research tool to measure the causal relationship between the financial and non-financial performance measures in comparison to other multivariate techniques. Although in the Malaysian business environment, the financial motive is still prominent, as compared to the non-financial aspects, the study has proved statistically there is causal link between financial and non-financial measures.